Adherent-invasive Escherichia coli in inflammatory bowel disease. Issue 3 (15th November 2017) - Palmela, Carolina; Chevarin, Caroline; Xu, Zhilu; Torres, Joana; Sevrin, Gwladys; Hirten, Robert; Barnich, Nicolas; Ng, Siew C; Colombel, Jean-Frederic
Abstract : Intestinal microbiome dysbiosis has been consistently described in patients with IBD. In the last decades, Escherichia coli, and the adherent-invasive E coli (AIEC) pathotype in particular, has been implicated in the pathogenesis of IBD. Since the discovery of AIEC, two decades ago, progress has been made in unravelling these bacteria characteristics and its interaction with the gut immune system. The mechanisms of adhesion of AIEC to intestinal epithelial cells (via FimH and cell adhesion molecule 6) and its ability to escape autophagy when inside macrophages are reviewed here. We also explore the existing data on the prevalence of AIEC in patients with Crohn's disease and UC, and the association between the presence of AIEC and disease location, activity and postoperative recurrence. Finally, we highlight potential therapeutic strategies targeting AIEC colonisation of gut mucosa, including the use of phage therapy, bacteriocins and antiadhesive molecules. These strategies may open new avenues for the prevention and treatment of IBD in the future.